DEKONSTRUKSI GENDER PERSPEKTIF RASYID RIDHA - Roswati Nurdin (IAIN Ambon, 2017)
The Book of Tafsir al-Manar originally is lectures material of tafsir al-Qur'an delivered by Muhammad Abduh in al-Azhar University, Egypt, which lasted from 1899 to his death (1905). The lectures are always attended by Rashid Rida, Abduh’s student, which every verse delivered by his teacher he noted in his mind. Furthermore, the records drawn up in writing then recorded and known as the Tafsir al-Manar, Rashid Rida using deconstruction theory in explaining the gender relations pattern when interpreting the verses of gender bias. Deconstruction theory in general can be understood as a demolition method to the reality containing the binary opposition logic. Binary opposition are two realities considered face to face, opposite and has a different position. This Paradigm explained the assumption of the existence of privilege embedded to the subject and underestimate the object, as the second class party. To provide its interpretation Rashid Ridha dismantle this Binary position logic method to re-position the women in accordance to the Qur'anic text desire. Key words: Deconstruction, Rashid Ridha, Tafsir al-Manar